Social media functionality as the indicators on fostering civic engagement - Abd Latib, Latifah; Bolong, Jusang; Ahmad Ghazali, Akmar Hayati; Osman, Mohd Nizam (Human Resource Management Academic Research Society, 2020)
The growth in the internet and social media development often seen and viewed as a radical shift in correspondence and a rehumanising aspect of communication. As a population expanded, the innovative application of social media has also drawn considerable attention to how communication is humanised and to promote civic engagement amongst digital societies. Even though social media have been praised for their potential for facilitating civic engagement, at a time most organisations are reluctant and unable to identify the functionalities of social media in developing humanise communication strategies and allocate resources to engage effectively. Therefore, a quantitative survey involved 400 respondents using purposive sampling technique has been done to investigate the usage and the functionalities of Facebooks as main predictors to build a humanise communication strategy towards promoting civic engagement. Based on multiple regression analysis, it highlighted that the group of six functionalities which are sharing, identity, groups, reputation, relationship and conversation were main contributions towards civic engagement. It is clearly explained that Facebook does not focus solely on just one function because it varies in terms of their functions and impact in promoting civic engagement. In conclusion, by analysing these predictive factors, government and organisations can understand how effective communication strategies should be developed in order to engage and promoting civic engagement among the digital communities.